Ensuring organisational and legal conditions for financing the social sector of Ukraine (Law and Safety, 2023)
The legal aspects of regulation of budgetary financing of social services have been analysed, and the main directions of improving the efficiency of the system of budgetary financing of social protection and social security of the population of Ukraine in modern conditions have been identified. Based on the analysis of scientific views, theoretical approaches to building a budget system in the context of social protection have been considered. The shortcomings of legal regulation of mechanisms for financing the provision of social protection services have been identified, and the main factors for improving the efficiency of budget financing and the inclusiveness of social protection have been described.The main task of the State in the context of social protection of the population is to fully and timely fill the relevant budgets and to finance social protection measures within the limits established by the budget. It has been noted that today the State system of budgetary funds management for financing social benefits remains one of the main components of the general and comprehensive social protection system of Ukraine. However, the practice of organising the budget process in Ukraine in the current socio-political conditions is characterised by an imbalance in the state and regional programmes of economic and social development. The main factors of disruptions in the functioning of the system of financing the social protection sector in Ukraine have been considered. There is a gradual reduction in the share of expenditures on social protection and social security from 30 % to 15 % of the consolidated budget in 2016–2022, while social spending is actually growing in monetary terms. It has been determined that although the Budget Code of Ukraine regulates the financial independence of local budgets by assigning to them the relevant sources of budget revenues, the actual level of revenue formation does not allow them to properly fulfil their own powers in the field of social protection of the population.It has been noted that in the context of decentralisation, amendments to the budget legislation should take into account the provision of real rights to pursue an independent socio-economic policy at the local level and at the same time ensure the effective exercise of their own and delegated powers. Provision of local and regional authorities with revenues sufficient to finance their powers should be done through decentralisation of budgetary funds, which will help to achieve a balance of regional and local budgets.
Keywords: budget process; social sphere; public funds; public financing; financial decentralisation; local self-government; local budgets.